1982
DOI: 10.1055/s-2007-1019009
|View full text |Cite
|
Sign up to set email alerts
|

The Hyperglycemic Effect of Thymosin F5, a Thymic Hormone

Abstract: The effect of thymosin F5, a partially purified thymic hormone, on the blood glucose level of rabbits was investigated. After the injection of thymosin F5 either I.V. or S.C., a state of hyperglycemia lasting for 9-10 hours was observed, and this was a dose-dependent effect. Also, the plasma 11-OH corticosteroid levels in thymosin F5 treated rabbits were found to be approximately threefold compared to the controls. Such a hyperglycemic effect was not observed in rabbits bilaterally surrenalectomized. These res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

1984
1984
1991
1991

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(2 citation statements)
references
References 5 publications
(6 reference statements)
1
1
0
Order By: Relevance
“…Although there was a slight increase in corticosterone 30 minutes after administration of 2 gg/kg of fraction 5, there was no sustained increase at two hours with this lower dose. In an independent study [37], a similar corticogenic effect of thymosin fraction 5 has been reported in rabbits. Thus, the phenomenon is reproducible and in different species.…”
Section: Evidence That Thymosins and Lymphokines Can Stimulate The Pisupporting
confidence: 55%
“…Although there was a slight increase in corticosterone 30 minutes after administration of 2 gg/kg of fraction 5, there was no sustained increase at two hours with this lower dose. In an independent study [37], a similar corticogenic effect of thymosin fraction 5 has been reported in rabbits. Thus, the phenomenon is reproducible and in different species.…”
Section: Evidence That Thymosins and Lymphokines Can Stimulate The Pisupporting
confidence: 55%
“…On the other hand, the thymic gland, is also known to play a fundamental role (Bach and Carnaud 1976;Archer and Pierce 1961;Trainin 1974) in the development and maturation of the immune system and to affect some metabolic processes (Potop, Boeru and Mreana 1966;Amici, Gianfranceschi, Marsili and Michetti 1974;Sivas, Uysal and Oz 1982). The thymic gland is also considered to synthesize an important portion of these functions through some hormones which it synthesized and secreted itself (Bach and Carnaud 1976;Goldstein 1976).…”
Section: Introductionmentioning
confidence: 99%